Go Mandalika: Digital Innovation of the Central Lombok Regency Tourism Office in Implementing Smart Branding of Local Destinations - Widiya Yuska; Mohammad Rezza Fahlevvi (CV. Abhinaya Indo Group, 2025)
Go Mandalika is a digital platform managed by the Central Lombok Regency Tourism Office to promote local tourist destinations. Despite its attractive features, Go Mandalika faces major challenges in terms of branding and content management due to the lack of human resources (HR) who are experts in digital marketing. This study aims to analyze the role of Go Mandalika as a digital promotion tool and how branding optimization can increase its visibility and effectiveness in promoting tourism in Central Lombok. Through literature review and content analysis, this study found that although Go Mandalika has great potential, problems in management and branding are the main obstacles. Therefore, recommendations from this study include strengthening branding, developing digital marketing HR, and more intense collaboration with external content to support regional promotion. This study is expected to contribute to improving the quality of government digital platform management in the tourism sector.